Discours et analyse du discours : une introduction - Frédéric Dion (Communiquer)
Discourse and Discourse Analysis, by Dominique Maingueneau, professor emeritus of linguistics at Sorbonne-Nouvelle University (Paris IV), is an introductory work that presents the main points of the author’s discourse theory . This synthesizing work aims to provide a basic, yet extensive understanding of discourse analysis, a discipline that is likely to be of interest to many scholars in communication sciences.